PERSEPSI ULAMA BANGKA BELITUNG TENTANG TEORI KHILAFAH DAN IMPLIKASINYA TERHADAP UKLHWAH ISLAMIYAH DAN UKHUWAH BASYARIYAH DALAM KEUTUHAN NKRI DI BANGKA BELITUNG - Suparta, Suparta (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Agama Islam Negeri Metro, 2018)
Abstract This study examines the perceptions of the Ulama ini Bangka Belitung about the concept of khilafah and its implications for Ukhwah Islmaiyah, Ukhuwah Basyariyah, and Ukhuwah Wathaniyah in the integrity of the Unity Republic of Indonesia in Bangka Belitung itself. As for the research method used in this study was field research. The results of the study show that the Bangka Belitung Ulema have the same majority perception of the establishment of the Islamic Khilafah, the Khilafah in Indonesia is still not enforceable because every ulama understands the Khilafah. This happened because the Ulama had no agreement and understanding about the Khilafah. The implications of the establishment of the Islamic Khilafah on Ukhwah Islmaiyah can lead to schismatic divisions among Muslims, the Implications of the Khilafah to Ukhuwah Basyariyah. where Indonesia has diverse tribes, races and religions. If the Khilafah is enforced upright it will become a horizontal conflict, namely the conflict between Muslims themselves and inter-religious conflict which makes the image of Muslims considered intolerant in the eyes of Indonesia and International. In addition, vertical conflict is the existence of conflict between Muslims who uphold the Khilafah with the Indonesian government and national figures and ulama who are Muslim who have not been Pro against the Caliphate. If this conflict occurs then what happens next is a split in the government and does not rule out the possibility of bloodshed. Finally, the implications for Ukhuwah Wathaniyah. In the slogan